PEMANFAATAN LIMBAH ORGANIK UNTUK PEMBUATAN ECO ENZYME PADA MASYARAKAT KELURAHAN BURAEN, KABUPATEN KUPANG - Bunga, Widasari; Kapa, Max J.; Simamora, Agnes V.; Kana, Yenny R.; Londingkene, Jesayas A.; Iburuni, Yohanes U. R. (Jurnal Abdi Insani, 2024)
Most of the people in Buraen Village rely on agriculture for their livelihoods, with seasonal land management, primarily focused on horticultural crops. Agricultural activities produce a significant amount of waste which can be utilized by the community to enhance farming practices. However, the management of agricultural waste itself has not yet received much attention from community. One form of agricultural waste processing technology that can be implemented is the production of eco-enzyme. The objective of this community service activity is to work with the target partners in processing organic waste from household and agricultural residues into eco-enzyme products. The approach applied in this program involves the transfer of information and technology through extension activities about eco-enzyme and its benefits in agriculture. In addition, the community is provided with training to develop skills in processing organic waste into eco-enzyme. The result of this activity show that the community in Buraen, as the target partner, gained an understanding of the concept of eco-enzyme and its utilization in agricultural practices. The community also acquired practical skills to process organic waste into eco-enzyme, which can be applied independently. With these skills, the community is expected to contribute to managing organic waste productively, reducing waste in the surrounding environment, and minimizing its negative impact. It is expected that this program will also raise community awareness about importance of environmental preservation. In conclusion, this program not only offers practical solutions for waste management but also supports the realization of environmentally friendly agricultural practices.